2008
DOI: 10.1523/jneurosci.3665-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Induces Long-Term Potentiation of Reactivity to Afferent Stimulation and Facilitates Epileptic Seizures in Rat Hippocampal Slices: Toward Understanding the Functional Consequences of Cerebrovascular Insults

Abstract: The effects of thrombin, a blood coagulation serine protease, were studied in rat hippocampal slices, in an attempt to comprehend its devastating effects when released into the brain after stroke and head trauma. Thrombin acting through its receptor, protease-activated receptor 1 (PAR1), produced a long-lasting enhancement of the reactivity of CA1 neurons to afferent stimulation, an effect that saturated the ability of the tissue to undergo tetanus-induced long-term potentiation. This effect was mediated by ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
119
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(131 citation statements)
references
References 34 publications
10
119
0
2
Order By: Relevance
“…Previous studies with hippocampal slices demonstrated that PAR1 activation positively regulates neuronal excitatory synaptic activity (Gingrich et al, 2000;Lee et al, 2007;Maggio et al, 2008;Mannaioni et al, 2008). To the best of our knowledge, there are no studies reporting PAR1-induced suppression of excitatory transmission.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous studies with hippocampal slices demonstrated that PAR1 activation positively regulates neuronal excitatory synaptic activity (Gingrich et al, 2000;Lee et al, 2007;Maggio et al, 2008;Mannaioni et al, 2008). To the best of our knowledge, there are no studies reporting PAR1-induced suppression of excitatory transmission.…”
Section: Discussionmentioning
confidence: 88%
“…At cellular levels, PAR1 activation influences synaptic transmission. PAR1 activation potentiated NMDA receptor currents (Gingrich et al, 2000;Mannaioni et al, 2008), induced long-term potentiation (LTP) of excitatory transmission (Maggio et al, 2008) in CA1 pyramidal neurons of hippocampal slices, and enhanced spontaneous release of glutamate onto substantia gelatinosa neurons in spinal cord slices (Fujita et al, 2009). As to the mechanisms, several studies have demonstrated that PAR agonists activate astrocytic PAR1, rather than neuronal PAR1, and induce glutamate release from astrocytes, thereby activating neuronal NMDA receptors in hippocampal acute slices (Lee et al, 2007;Mannaioni et al, 2008;Shigetomi et al, 2008) and hippocampal coculture preparations (Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that accumulated albumin binds to transforming growth factor beta receptor 2 (TGFbetaR2) in astrocytes and induces rapid astrocytic transformation and dysfunction David et al, 2009;Ivenset al, 2007;) In addition, leakage of some other serum-derived components into the extracellular space may also result in hyperexcitability and seizure onset. For example, it has been recently shown that the serum protein, thrombin, via receptors protease-activated receptor 1 (PAR1), produces a long-lasting enhancement of the reactivity of CA1 neurons to afferent stimulation (Maggio et al, 2008). It should also be noted that in many cases of epilepsy, that BBB breakdown has been associated with early or delayed neuronal damage (Rigau et al, 2007;Tomkins et al, 2007;van Vliet et al, 2007).…”
Section: Blood Brain Barrier Permeability and Epilepsymentioning
confidence: 99%
“…Thrombin, a serine protease essential in the coagulation cascade is involved in the production of seizures 6 . It was demonstrated that active thrombin injected into rat brains resulted in both electrographic and clinical seizures 7 .…”
mentioning
confidence: 99%
“…It was demonstrated that active thrombin injected into rat brains resulted in both electrographic and clinical seizures 7 . It was proposed that thrombin, acting on its receptor, protease-activated receptor 1 (PAR1), has marked effects on the production of long-term potentiation (LTP) in responses to afferent stimulation and that it enhances the sensitivity to epileptic seizures in brain slices 6 . Thrombin may triggers the generation of epileptic seizures by reducing the inhibitory and increasing the excitatory tone in CA3 neurons 5,8,9 .…”
mentioning
confidence: 99%